Different Relationship between hsp70 mRNA and hsp70 Levels in the Heat Shock Response of Two Salmonids with Dissimilar Temperature Preference - Lewis, Mario; Götting, Miriam; Anttila, Katja; Kanerva, Mirella; Prokkola, Jenni M.; Seppänen, Eila; Kolari, Irma; Nikinmaa, Mikko (Frontiers in Physiology, 2016)
The heat shock response (HSR) refers to the rapid production of heat shock proteins (hsps) in response to a sudden increase in temperature. Its regulation by heat shock factors is a good example of how gene expression is transcriptionally regulated by environmental stresses. In contrast, little is known about post-transcriptional regulation of the response. The heat shock response is often used to characterize the temperature tolerance of species with the rationale that whenever the response sets on, a species is approaching its lethal temperature. It has commonly been considered that an increase in hsp mRNA gives an accurate indication that the same happens to the protein level, but this need not be the case. With climate change, understanding of the effects of temperature on gene expression of especially polar organisms has become imperative to evaluate how both biodiversity and commercially important species respond, since temperature increases are expected to be largest in polar areas. Here we studied the HSR of two phylogenetically related Arctic species, which differ in their temperature tolerance with Arctic charr having lower maximally tolerated temperature than Atlantic salmon. Arctic charr acclimated to 15°C and exposed to 7°C temperature increase for 30 minutes showed both an increase in hsp70 mRNA and hsp70 whereas in salmon only hsp70 mRNA increased. Our results indicate that the temperature for transcriptional induction of hsp can be different from the one required for a measurable change in inducible hsp level. The species with lower temperature tolerance, Arctic charr, are experiencing temperature stress already at the higher acclimation temperature, 15°C, as their hsp70 mRNA and hsp70 levels were higher, and they grow less than fish at 8°C (for salmon the opposite is true). Consequently, charr experience more drastic heat shock than salmon. Although further studies are needed to establish the temperature range, and length of exposure, where hsp mRNA and hsp level are disconnected, the observation suggests that by measuring both hsp mRNA and hsp level, one can evaluate if a species is approaching the higher end of its temperature tolerance and thus, an organism's vulnerability to the challenges imposed by elevated water